FONDUL DE BIBLIOFILIE CONTEMPORANĂ: ASPECTE DE POPULARIZARE ŞI VALORIFICARE - COSTIUC, Tatiana (BIBLIOPOLIS, 2020)
This article approaches some aspects of valorification of the bibliophily funds of the County library Octavian Goga, Cluj, which include donation from Cluj personnalities and personal libraries of some scientists, professors from Cluj. The special collection is included in the aquisition’s politic of the library and follows the steps: document evaluation, destination and integration in the library collection or distribution to others libraries. The material presents the others ways of valorification: the online catalogue, bibliographical newsletters, elaboration of studies and articles about the collection content and the access.